Synthesis of 4-aminotetrahydropyran scaffolds for drug discovery. Issue 7 (1st April 2017) - Nortcliffe, Andrew; Milne, Gavin D.S.; Hamza, Daniel; Moody, Christopher J.
Graphical abstract: Abstract: Functionalised tetrahydropyran scaffolds were prepared using a tethered enol-ether Prins cyclisation and elaborated to show their potential use in library synthesis. The key 4-hydroxytetrahydropyran scaffold could be readily manipulated to the 4-azidotetrahydropyran that could be elaborated via copper catalysed azide-alkyne cycloaddition or by reduction to the amine, to provide sp 3 -rich scaffolds useful for drug discovery.